Comprehensive analysis of Maharashtra's urban areas' online platform purchase trends (International Journal of Food and Nutritional Sciences, 2022)
: Online marketing appertain the growth of creating a tailored content in online platforms for promoting and endorsing a product. Currently this method of marketing plays a vital role than traditional marketing. Online ads and social media influencers colonize the most effective forms of social media marketing in swaying consumers purchasing decisions. Moreover, user-generated content in online platforms also plays a vital role in shaping the opinions and perceptions of consumers about a product.